2016
DOI: 10.1074/jbc.m116.728840
|View full text |Cite
|
Sign up to set email alerts
|

Blunting Autoantigen-induced FOXO3a Protein Phosphorylation and Degradation Is a Novel Pathway of Glucocorticoids for the Treatment of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease affecting multiple organs. Glucocorticoids (GCs), the potent anti-inflammatory drugs, remain as a cornerstone in the treatment for SLE; nevertheless, their clinical efficacy is compromised by the side effects of long term treatment and resistance. To improve the therapeutic efficacy of GCs in SLE, it is important to further decipher the molecular mechanisms of how GCs exert their anti-inflammatory effects. In this investigation, FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Immunoprecipitation was performed as described previously (67,68). Briefly, cells were lysed in RIPA buffer (50 mM Tris at pH 8.0, 280 mM NaCl, 0.5% NP-40, 2 mM EDTA, 10% glycerol,(1.2 M NaCl, 60 mM EDTA, 30% sucrose, 26% PEG) was added to each tube and incubated at 4°C for at least 1 h before pelleting of the core particles by centrifugation at 7,300 ϫ g for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation was performed as described previously (67,68). Briefly, cells were lysed in RIPA buffer (50 mM Tris at pH 8.0, 280 mM NaCl, 0.5% NP-40, 2 mM EDTA, 10% glycerol,(1.2 M NaCl, 60 mM EDTA, 30% sucrose, 26% PEG) was added to each tube and incubated at 4°C for at least 1 h before pelleting of the core particles by centrifugation at 7,300 ϫ g for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Lu's studies showed that FOXO3a was a downregulated molecule in SLE patients, while FOXO3 was upregulated by glucocorticoids (GCs), which relied on the suppression of pI3K/AKT-mediated FOXO3a phosphorylation. In one of their other studies, FOXO3a plays an important role in the GC-mediated inhibition of NF-B activity, which might involve FOXO3a interaction with NF-B p65 protein [11]. The study reported that B-cell epitopes,named 2-1, an altered isoform, showed lower levels of phosphorylation in SLE patients, which may be related to the pathogenesis of SLE; it also demonstrated that higher concentrations of phosphoproteins are found in the cell membrane and nucleus and that 50 nucleic acid metabolic pathways are modi ed during the pathogenesis of SLE, speci cally the MAPK signaling pathway, which leads to abnormal intracellular signaling [12].…”
Section: Discussionmentioning
confidence: 96%
“…Since the discovery of phosphorylation, many new PTMs have been identi ed over the years, such as crotonylation, propionylation, malonylation, butyrylation, succinylation, glutarylation, βhydroxybutyrylation and 2-hydroxyisobutyrylation [9]. PTMs have been found in different pathologic conditions in SLE [10,11]. Lu's studies showed that FOXO3a was a downregulated molecule in SLE patients, while FOXO3 was upregulated by glucocorticoids (GCs), which relied on the suppression of pI3K/AKT-mediated FOXO3a phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In one of their other studies, FOXO3a plays an important role in the GC-mediated inhibition of NF-B activity, which might involve FOXO3a interaction with NF-B p65 protein (Lu et al 2016). The study reported that 2 − 1, an altered isoform, showed lower levels of phosphorylation in SLE patients, which may be related to the pathogenesis of SLE; it also demonstrated that higher concentrations of phosphoproteins are found in the cell membrane and nucleus and that 50 nucleic acid metabolic pathways are modified during the pathogenesis of SLE, specifically the MAPK signaling pathway, which leads to abnormal intracellular signaling (Routsias and Tzioufas 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Since the discovery of phosphorylation, many new PTMs have been identified over the years, such as crotonylation, propionylation, malonylation, butyrylation, succinylation, glutarylation, βhydroxybutyrylation and 2-hydroxyisobutyrylation (Wu et al 2018). PTMs have been found in different pathologic conditions in SLE (Lu et al 2016;Zavala-Cerna et al 2014). Lu's studies showed that…”
Section: Discussionmentioning
confidence: 99%